A study on pest control implementation and operation for different types of building / Wan Nor Adeebah Wan Ibrahim - Wan Ibrahim, Wan Nor Adeebah (Faculty of Architecture, Planning and Surveying, 2008)
Pests are generally defined as living organisms that are found at the wrong place and time. Pests normally enter the house in search of food and the house becomes a harborage for them to hide and breed. Despite all the technological advances of the past half century, the researcher has not come very far in the battle against critters. Pest control is actually refers to the regulation or management of another species defined as a pest, usually because it is believed to be detrimental to a person’s health, the ecology or the economy. Pest control is also at least as old as agriculture. In order to maximize food production, it can be economically advantageous to protect crops from competing species of plants, as well as from herbivores competing with humans. In April 1944, a Better Homes and Gardens magazine article suggested readers handle moles this way: "You can dig them out if you're patient. And if you are mad enough about what a mole has done to your lawn and flowers, you won't mind in the least giving him the knockout with the flat of your spade. Wait until you see the soil heaving and are sure which way he's headed.